(untitled) (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2016)
The Roman Erotic Elegy is a topic that has been widely researched by scholars from areas related to Classical Studies. However, the researches usually concern on the poetic issue related to the elegiac genre, or they address to elegiac authors and their compositions. In this literary genre, especially when it comes to love poetry, the themes always relates to women, lovers and their moral behaviors and ideals, which arouses the curiosity of other women for this type of reading. What this love poetry can tell us about the education of women? In this sense, the objective of this study concerns to the erotic elegy and their possibility of contributing to the education of Roman women.